Myeloid PDLIM2 repression as a common mechanism of infection susceptibility in lung diseases - Gao, Feng; Liu, Xujie; Sun, Fan; Xiao, Yadong; Xiao, Gutian; Qu, Zhaoxia (Frontiers in Immunology, 2025)
IntroductionThe PDZ-LIM domain-containing protein PDLIM2 serves as a unique tumor suppressor and immune modulator. Its repression in either lung epithelial or myeloid cells has been shown to promote lung cancer and therapy resistance. However, whether PDLIM2 plays a broader role in other lung diseases remains unclear.MethodsGene expression data on human samples were exploited to investigate if PDLIM2 is repressed in the lung of patients with chronic obstructive pulmonary disease (COPD) or interstitial lung disease (ILD/idiopathic pulmonary fibrosis (IPF). PDLIM2 conditional knockout (KO) mice and wild type (WT) control mice were intratracheally instilled with the bacterial endotoxin lipopolysaccharide (LPS) to induce acute lung injury (ALI), a murine model of human acute respiratory distress syndrome (ARDS) that can also provide mechanistic insights into COPD, pulmonary fibrosis (PF) and infectious disease. Kaplan-Meier estimator was used to determine animal survival rate, and histological analysis and single-cell RNA sequencing (scRNA-seq) of mouse lung tissues were performed to systematically define the roles of PDLIM2 at the population and single-cell level. Ex vivo phagocytosis and neutrophil extracellular trap (NET) formation assays were also performed to validate the scRNA-seq analysis.ResultsPDLIM2 was repressed in the lungs of COPD and ILD/IPF patients, and this repression was associated with disease severity. Selective deletion of PDLIM2 in myeloid cells rendered mice more vulnerable to lung injury and mortality by LPS intratracheal instillation. The increased susceptibility was linked to exacerbated pro-inflammation signaling and diminished anti-inflammation signaling in the lung, and particularly, in lung macrophages and neutrophils.ConclusionsPDLIM2 plays an indispensable role in preventing ALI/ARDS and death, and its repression is associated with COPD and ILD progression. These data suggest that PDLIM2 repression, especially in lung myeloid cells, is a common mechanism driving COPD, ILD/IPF, and lung cancer and increasing patients’ susceptibility to infection.